The complete plastid genome of cherry plants Prunus discoidea (Rosaceae) and its phylogenetic implication. Issue 2 (3rd July 2019) - Li, Meng; Song, Yan-Feng; Zhu, Shu-Xia; Zhu, Hong; Yi, Xian-Gui; Chen, Zhang-Chi; Li, Ming-Zhi; Wang, Xian-Rong
Abstract: Prunus discoidea is an endemic cherry species with ornamental value, spread in eastern China (Anhui, Jiangxi, Zhejiang provinces). Little information is available regarding its genomic, with limited phylogenetic relationship study performed on P. discoidea until now. The plastid genome was 158, 024 bp in length consisting of four regions: large single-copy region (85, 953 bp), small single-copy region (19, 113 bp), and a pair of inverted repeat regions (26, 469 bp each). The plastid genome contained a total of 129 genes, including 84 coding genes, 8 rRNA genes, and 37 tRNA genes. Phylogenetic analysis for 20 reported genomes within the Prunus sensu lato showed three main clades of Prunus s.l. with strong supports.